Identifying Tax Efficient Supply Chain Management Practices in Cross-Border Transactions - Waluyo, Waluyo (International Journal of Supply Chain Management, 2018)
The objective of this study is to explore the efficient supply chain management practices. The current study examined low supply chain cost and supply chain agility as efficient supply chain management practices in Indonesia. Moreover, the moderating effect of tax was also examined. Primary data were collected from employees of supply chain companies. Thus, a quantitative research approach was used. Total 300 questionnaires were distributed among the employees of supply chain companies. Findings of the study revealed that low supply chain cost and supply chain agility effect significantly on international sales among Indonesian supply chain companies. Low supply chain cost and increase in supply chain agility have a positive contribution towards international sales related to the supply chain. However, a tax has a negative influence on cross-border transactions or international sales. It significantly decreases the positive effect of low supply chain cost and supply chain agility on international sales.